Crack suppression by natural fiber integration for improved interlaminar fracture toughness in fiber hybrid composites - Anant Joshi; P S Shivakumar Gouda; I. Sridhar; Umarfarooq M A; Vinayak Uppin; Jyoti Vastrad; Nabaneeta Gogoi; Abhilash Edacherian (Fracture and Structural Integrity)
In this paper, the effect of integration of natural fibers in UD carbon fiber is studied. The integration of natural fibers in carbon fiber is made via intra fiber hybridization. Natural fiber hybrid composite samples were prepared for Mode I and Mode II fracture tests. XRD analysis was done for the chosen natural fibers to know the crystallinity index and then compared with Carbon and Glass fibers. The fracture test experimental results, revealed that the effect of Jute fiber integration in UD Carbon epoxy composite was found significant in getting relatively good Mode I and II fracture toughness at the crack initiation without losing its stiffness. In addition to this Kenaf Carbon epoxy composite indicated better crack suppression with 30% higher propagation toughness values as compared to other hybrid combinations and pristine composites. It is observed that integration of jute fibers in UD carbon epoxy composites was significant in achieving good mode I and mode II fracture toughness at the crack initiation without losing its stiffness and also kenaf carbon epoxy composites indicated better crack suppression with 30% higher propagation toughness as compared to other hybrid combinations used.